Bibliometric analysis of T cells in allergic rhinitis - Liu, Shuang; Hu, Xiaoyan; Zhang, Jing; Lv, Liangge; He, Yuxiao; Jiang, Liang; Qin, Gang (Heliyon, 2024)
By reviewing the relevant literature in the field of T cell and allergic rhinitis, we determined the development status, study hotspots, and research frontiers viewpoints of this field to provide a reference for researchers and clinical workers. Methods: Web of Science Core Collection (WoSCC) was applied to obtain the studies related to T cells and allergic rhinitis (AR) from 2003 to 2023, and the information extracted from these studies was analyzed using CiteSpace 6.1. R6 and VOSviewer 1.6.18. Results: In total, 1585 articles were collected from WoSCC, with the time set between 2003 and 2023. Overall, a growing number of articles are being published annually. The countries and institutions with the maximum publications volume are China (370, 23.34 %) and Sun Yat-sen University (34, 2.15 %). The biggest contributor to the field was Durham, Stephen R. from the UK (22, 1.39 %). The Journal of Allergy and Clinical Immunology published the most related papers in the field (88, 5.54 %). Immunotherapy, Th cells, and inflammation were found to be the research hotspots in this area of T cells and allergic rhinitis in recent years. Pathway, model, Regulatory T cells (Treg cells), regulatory B cells, immunoglobulin E,and innate lymphoid cells were the current research hotspots in this field. Conclusion: The field of T cell and allergic rhinitis is developing rapidly, and many countries significantly contributed to this field. Most researchers in this field mainly focused on immunotherapy, Th cell, and inflammation. Pathway, model, Treg cell, regulatory B cell, immunoglobulin E,and innate lymphoid cells were the main subject of current research, and future development is expected to occur in this field.